Robustness of frequency domain image watermarking against image processing attacks - Chai, Jee Sing (Universiti Malaysia Sarawak (UNIMAS), 2008)
Since there is an issue about none of robust digital watermarking uses the same robustness criteria, and consequently causes a non-practical comparison as well as slow down progress in this area. Generally, the schemes in spatial domain are usually less robust to attacks; while the schemes in frequency/transform domain are more robust to kinds of distortions. Synchronization errors can lead to significant performance loss of known image watermarking methods, which can be evidenced by the spurious effects that the suite of signal processing or transformation attacks contained in the benchmark software Stirmark. Thus, in order to provide a fair benchmark for image watermarking systems, a comparison technique using the most fundamental robust frequency domain schemes (DeT, DWT and FFT) are presented in this projecj Experimental results provide the comparisons when two different sized watermarKs are embedded into a grayscale image, and then show the watermark performance evaluation in such a way that fair comparisons between different frequency domain schemes are possible. Base on the performance of different watermarking schemes, a combination of watermarking scheme that is robust against both signal processing a:nd transformation attacks is evaluated.